The Application Of Physical Fitness Test Measurements Using A Futsal Sports Branch - Salsabilla, Nabila Shafa; Hartati, Hartati; Destriana, Destriana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The physical condition of students significantly influences futsal performance. This study aims to establish normative categories for assessing physical test results in futsal using an application. Employing a quantitative research approach with a survey method, the sample consisted of 30 sixth-grade students from State Elementary School 184 Palembang, comprising 14 male and 16 female students. Findings revealed that, among the sixth-grade students, speed was classified as very poor (90%), agility as very good (100%), explosive power as very good (93%), strength as less (53%), and endurance as sufficient (37%) in the context of futsal sports.